The Influence of Project-Based Learning Model on Student Creativity in Learning Design: A Literature Review - Rati Andilah; Tifaldi Akbar; Suci Ramadon; Ripi Apandi; Rando Wijaya (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
Creativity has emerged as a critical competency for higher education graduates navigating the demands of Society 5.0 and increasingly automated labor markets. This literature review examines the influence of Project-Based Learning (PjBL) on student creativity within instructional design contexts, synthesizing contemporary scholarly discourse from 2020 to 2026. Employing a narrative-integrative approach, literature was systematically retrieved and analyzed from Google Scholar using targeted Boolean search strategies. Findings indicate that PjBL significantly enhances multidimensional creativity, particularly fluency and flexibility, while originality and elaboration depend heavily on deliberate instructional scaffolding. Instructional design functions as a critical mediating architecture, where constructive alignment, iterative feedback loops, and formative assessment protocols transform open-ended projects into structured creativity incubation environments. However, intervention effectiveness remains contingent upon institutional infrastructure, faculty pedagogical readiness, and equitable digital access. The review concludes that PjBL’s creative potential is maximized only when pedagogical intent is rigorously operationalized through evidence-based design frameworks. Recommendations emphasize longitudinal tracking, standardized creativity metrics, targeted faculty development, and ethical AI integration. This synthesis provides actionable insights for curriculum designers and educators seeking to systematically cultivate creative competencies in alignment with future workforce demands.